If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-24=-6(7v-3)+5v
We move all terms to the left:
-24-(-6(7v-3)+5v)=0
We calculate terms in parentheses: -(-6(7v-3)+5v), so:We get rid of parentheses
-6(7v-3)+5v
We add all the numbers together, and all the variables
5v-6(7v-3)
We multiply parentheses
5v-42v+18
We add all the numbers together, and all the variables
-37v+18
Back to the equation:
-(-37v+18)
37v-18-24=0
We add all the numbers together, and all the variables
37v-42=0
We move all terms containing v to the left, all other terms to the right
37v=42
v=42/37
v=1+5/37
| 14·y·1=14y | | 10x+4+x=11x−1 | | |0.5x+1.5|=-0.5 | | a–2=-15 | | 1=t/2- | | x-14/3x+24=0 | | (m/6)-4=-3 | | C=15n+450 | | (8x+14)+(12x-50)=80 | | 7x−30=19 | | 3x+12.2=18.5 | | 10-5v=20 | | x^2=3x*4 | | 3x+12.2=18.6 | | C(x)=20x+50 | | 7x+1+10x-32=90 | | x^2=x(x) | | (9x+5)=(12x-19)° | | 10+y/4=18 | | 196=-16t^2+196(0) | | 7(3w+5)/4=6 | | 7x+1+10x-32=180 | | 5(x*17)=$1,495 | | 12c-11=49 | | 98=x10 | | -8f=7-9f | | 52+2x=x+40 | | 3x+9-5=27 | | -n-2=-9n-10 | | 0y=0X+0 | | √(5-x)-1=x | | h/2-6=5 |